Perbedaan Prestasi Belajar Siswa Yang Rajin Membaca Dan Tidak Rajin Membaca Pada Mata Pelajaran PPkn Siswa Sekolah Dasar - Dian Eka Indriani (Penerbit STKIP PGRI Bangkalan, 2017)
In this study, used types of quantitative research, with the goal to determine differencesthat Diligent Student Achievement is Reading and Reading graders Not Diligent V. In thisstudy there was no special treatment of the research object. The population or the entiresubject in this study were students of class V Public Elementary School District 01 DistrictBanyuates Lacker school year 2015/2016 with a total population of 32 students. Thesample in this study was all students of class V SD Negri 01 Academic Year 2015/2016Banyuates District of Sampang numbered as many as 32 students. To prove theadmissibility of the value t table hypothesis tested by t-test analysis results of hypothesistesting as follows. From these results obtained t = 1.813 and the outcome of the t-countvalue is smaller than the table level significant 5% with N = 32-2(D.b = 30) is 2,042 sorefused Hypothesis alternative (HA) and accept the null hypothesis (H0), so it can beconcluded that there is no difference significant between student achievement are diligentlyread and diligently read in class V SDN country 01.